Countermeasures to the cardiometabolic impairments associated with sleep and circadian disruption - Seward, Sophie Lynn, author; Broussard, Josiane L., advisor; Blankenship, Jennifer M., committee member; Foster, Michelle T., committee member; Moreau, Kerrie L., committee member (Colorado State University. Libraries, 2024)
Sleep and circadian disruption are widespread and have both been recognized as independent risk factors for cardiometabolic diseases, including cardiovascular disease and type 2 diabetes. Circadian misalignment, defined as a mismatch between the endogenous circadian system and external behavioral/environmental factors such as sleep, energy intake, activity and light, is one mechanism suggested to increase the risk of cardiometabolic disease risk during combined sleep and circadian disruption. In some populations, such as night shift workers, sleep and circadian disruption are often unavoidable and lead to an increased risk for cardiovascular disease and type 2 diabetes. Therefore, strategies are needed to mitigate the negative impact of sleep and circadian disruption on cardiometabolic disease risk. The following dissertation is comprised of a series of experiments with the overall aims to (1) examine the acute cardiometabolic impairments associated with sleep and circadian disruption; and (2) investigate a potential countermeasure to mitigate cardiometabolic impairments when sleep and circadian disruption are unavoidable. Several study designs were employed to address the aims of this dissertation. In the first investigation, a quasi-randomized crossover study was conducted in a free-living setting to compare blood pressure in adults during a 24h period during both a day shift versus a night shift. Because elevated blood pressure is an important CVD risk factor, throughout this study blood pressure was measured every 30 minutes to assess 24h, waking, and sleeping levels. In the second study, a 2-week consecutive design experiment was conducted in healthy adults to examine the impact of altered meal timing on cardiometabolic health. During Week 1, participants consumed energy over a 13h period with meals individually anchored to habitual wake time. In week 2, participants matched their food intake from week 1 but restricted intake to an 8h period. At the end of each week, participants were admitted to the laboratory for an in-patient overnight stay where hourly blood samples were collected and assayed for circulating factors including glucose, insulin, and lipid species. This alteration in meal timing was then employed in another study where participants underwent a simulated nightshift work protocol. In this study, participants underwent a 6d randomized crossover inpatient study with at least 1 month between conditions. In one condition, participants ate during the biological night as typically done during night shift work (circadian misalignment). In the other condition, participants consolidated meals to the biological daytime (circadian misalignment + time restricted eating), while still providing the same sleep opportunity and diet. Consolidating food intake to the biological daytime, particularly in night shift work, was hypothesized to reduce the risk of cardiometabolic disease by reducing the mismatch between the endogenous circadian system and external behaviors. Major themes emerging from these studies are that as little as one night of shift work in a free-living setting is sufficient to induce multiple CVD risk factors including increased BP and reduced sleep duration in healthy adults. Furthermore, data presented throughout this dissertation suggest daytime eating during sleep and circadian disruption, within a highly controlled laboratory setting, improves important markers of cardiometabolic health including blood pressure. Data presented here indicates that meal timing interventions may be a potential countermeasure to improve cardiometabolic health in conditions of circadian disruption. However, more research is needed in a free-living shift work population. Additionally, future research should explore how other countermeasures may improve cardiometabolic health when sleep and circadian disruption are unavoidable. Overall, work presented throughout this dissertation underscores the urgent need for effective strategies to mitigate cardiometabolic risks associated with sleep and circadian disruption, especially in vulnerable populations such as night shift workers.